How to Counter a Counterstory (and Keep Those People in Their Place) - Lindemann, Hilde (Narrative Works, 2015)
On October 27, 2014, Hilde Lindemann presented the John McKendy Memorial Lecture on Narrative at St. Thomas University. The annual lecture, sponsored by the Centre for Interdisciplinary Research on Narrative (CIRN), is named for John McKendy, PhD, a member of the Sociology Department at St. Thomas University and one of the founding members of CIRN, who died tragically in 2008. Dr. Lindemann’s lecture focused on narrative strategies that people in dominant social positions use to counter a counterstory and keep an oppressive social order in place. A counterstory is “a story that is told for the purpose of resisting a socially shared narrative that purports to justify the oppression of a social group ... The socially shared story—master narrative—enters the tissue of stories that constitute the group’s identity, damaging that identity and so constricting group members’ access to the goods on offer in their society.” In her lecture, she explored some of the difficulties that arise when a counterstory sets out to repair that identity, and why the master narratives are so difficult to uproot. Dr. Lindemann has kindly agreed to have the video of her lecture published in Narrative Works.